Nursery management in vegetable crops for enhancing farmers’ income - Chaurasia, S N S; Bahadur, Anant; Sharma, Swati; Krishna, Hare; Singh, S K (Indian Horticulture, 2023)
The production of healthy seedlings plays a vital role in the establishment of a healthy crop in the main field. Nursery management of vegetable crops is primary and most important aspect in enhancing vegetable production and profitability. Majority of germinating tender saplings get damaged due to certain biotic and abiotic factors in the process of nursery raising due to which farmers incur great loss. Farmers are still following their age old traditional method of nursery raising of vegetables. Farmers of Diara region are compelled to raise their vegetable nursery at very limited and specified places located at higher elevation due to threat of floods every year and 60-70% saplings are lost. This article focusses on nursery management in vegetable crops to enhance the income and reduce losses.